2011
DOI: 10.1021/ef200416e
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Modeling Study of Sulfur Capture by Limestone in Selected Conditions of Air-Fired and Oxy-fuel Circulating Fluidized-Bed Boilers

Abstract: The influence of different conditions on the sulfur-capture efficiency during fluidized-bed desulfurization was studied using both experimental and modeling methods. The effects of the temperature (∼1120 or ∼1200 K) and gas atmosphere (90% N2 or 90% CO2) were studied using one limestone type. The CO2 atmosphere increased the degree of conversion compared to traditional air combustion conditions using both calcination–sulfation and direct sulfation methods. The scanning electron microscopy–energy-dispersive spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 18 publications
5
45
0
Order By: Relevance
“…The dense CaSO 4 is the main reason for relatively low calcium utilisation for sulphur capture in fluidised bed combustion applications. It has been observed also in earlier experimental work [5][6] that the sulphur capture is worse in direct sulphation region but capture is enhanced by higher CO 2 partial pressure in indirect sulphation region. Only conditions in test 5 were clearly on CaCO 3 side of CaCO 3 -CaO equilibrium curve, when sulphur is directly captured by CaCO 3 without calcination.…”
Section: Pilot Scale Cfbsupporting
confidence: 69%
“…The dense CaSO 4 is the main reason for relatively low calcium utilisation for sulphur capture in fluidised bed combustion applications. It has been observed also in earlier experimental work [5][6] that the sulphur capture is worse in direct sulphation region but capture is enhanced by higher CO 2 partial pressure in indirect sulphation region. Only conditions in test 5 were clearly on CaCO 3 side of CaCO 3 -CaO equilibrium curve, when sulphur is directly captured by CaCO 3 without calcination.…”
Section: Pilot Scale Cfbsupporting
confidence: 69%
“…Organically associated Ca can recapture the H 2 S to form sulfidic sulfur at temperatures above 873 K. Pyrolysis at temperatures of 873-1073 K, of ion-exchanged acid-washed coals with calcium acetate solution has revealed a significant increase of the sulfidic sulfur in the char [253]. In fluidized bed gasification/combustion, the role of Ca-based sorbent such as limestone or dolomite in capturing H 2 S/SO 2 has been well documented [254][255][256][257][258]. Given the high content of AAEM in some biomass fuels, sulfur capture by these metals could be an added advantage of co-conversion of coal and biomass based fuels.…”
Section: Effect Of Blending Coal and Biomass/waste On The Fate Of Sulmentioning
confidence: 99%
“…A calcination and sulfation model established by Keener et al [32] showed that calcination had an influence on sulfation of limestone in typical air-fired CFBB conditions, but how calcination was influenced by sulfation was not described. Several experiments were conducted by Rahiala and Takkinen [33,34] with a bench-scale bubbling fluidized-bed reactor to study the influence of temperature and CO 2 concentration on sulfur capture of limestone, but bubbling fluidized-bed reactor cannot give precise chemical kinetics curves to analyze every stage of the reaction, and more importantly, their tests did not focus on the condition in real air fired CFBBs. An investigation by Olas et al [35] on mechanical activation of limestone under high concentrations of CO 2 in CFBB found that both the diffusion of SO 2 and CO 2 could be limited by the formation of CaSO 4 layer on the surface of the limestone particles, and mechanical treatment may increase both the sorbent calcination and sulfation rates.…”
Section: Introductionmentioning
confidence: 99%